Transient Simulation to Analyze Wax Deposition and Flow Pattern Behavior Along Tubing Under Esp Installation and Gassy Well Condition - Brian Tony; Steven Chandra; Rafael J.S. Purba; Muhammad Fadhlan Solihan; Ega Dimas Saputra (Scientific Contributions Oil and Gas, 2025)
Wax deposition is a common phenomenon that restricts flow in tubing, causing production decline. In the studied well, this decline is linked to wax thickness increasing from 0.0021 inches (Day 1) to 0.0114 inches (Day 7), occurring as fluid temperatures drop below 153.5°F. An Electrical Submersible Pump (ESP) is used to address this, but it impacts thermal conditions and flow behavior, especially in gassy wells. Therefore, a transient simulation is required to analyze wax deposition and flow behavior under ESP installation. This study performs a 7-day transient simulation using OLGA 2022.1.0 on the "X" well, a gassy well (700 scf/bbl GOR) with 38% wax content, utilizing a 70-stage DN610 ESP. Results show wax deposition begins on Day 1 (max 0.0021 inches) and thickens to 0.0114 inches by Day 7. Flow patterns vary along the tubing: stratified flow is dominant from the pump setting depth to KOP, while slug flow dominates from KOP to the tubing head. Annular flow was observed at the tubing head on several days. Sensitivity analysis revealed that more ESP stages result in more wax deposition. This is because the ESP increases the production rate; as more oil flows, more contained wax precipitates and deposits. The least wax was observed in the scenario with no ESP. This work demonstrates how ESP-induced liquid holdup and slug/annular transitions accelerate wax deposition and emphasizes the importance of transient simulation in predicting production risks.